Substance use and related risk behaviors among junior high school students in Nakhon Pathom province, Thailand - Paranee Ninkron; Shamsudeen Yau; Praphan Khuntiterakul; Benchamaphorn Nakamadee (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The spread of drug use has been consistently increasing in Asia, posing a serious public health problem, especially among new addicts. In Thailand, the problem has persisted for decades leading to a consistent decline in the age of drug use initiation, making drug use an important social problem, especially among youngsters. This study aimed to examine the factors related to substance abuse risk behaviors among lower secondary school students. Design/methodology/approach - A cross-sectional survey was conducted using a self-administered questionnaire to collect the data from a sample of 624 students aged 12 through 18 years. Data analysis was performed using descriptive statistics and multiple linear regression to identify factors related to substance use risk behaviors. Findings - Factors associated with drug use risk behavior were access to drugs (0.882; <0.001), which had the highest predictive power, family relationships (−0.555; <0.001), self-esteem (−0.516; <0.001) and awareness about drugs (−0.412; <0.005). Originality/value - Prevention interventions that incorporate reducing access to drugs, strengthening family ties, boosting adolescents' self-esteem and increasing their awareness about drugs should be tailored to target homes, schools and communities. As the problem appears to be multidimensional, the full participation of all relevant stakeholders such as teachers, parents, religious and community leaders in the intervention programs is as essential as the interventions themselves.